2012
DOI: 10.1016/j.ijrobp.2012.07.1486
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy (SBRT) for Lung Malignancies: Preliminary Toxicity Results Using a Flattening Filter-free Linear Accelerator Operating at 2400 Monitor Units per Minute

Abstract: Background: Flattening filter-free (FFF) linear accelerators (linacs) are capable of delivering dose rates more than 4-times higher than conventional linacs during SBRT treatments, causing some to speculate whether the higher dose rate leads to increased toxicity owing to radiobiological dose rate effects. Despite wide clinical use of this emerging technology, clinical toxicity data for FFF SBRT are lacking. In this retrospective study, we report the acute and late toxicities observed in our lung radiosurgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It seems to be partly because the number of the subjects of this study was small, the stage and tumor diameters had a wide range, and the observation period was short. Prendergast et al reported that there was no significant difference between the two treatments, and Rieber et al pointed out the same cause as us (40,41).…”
Section: Discussionmentioning
confidence: 74%
“…It seems to be partly because the number of the subjects of this study was small, the stage and tumor diameters had a wide range, and the observation period was short. Prendergast et al reported that there was no significant difference between the two treatments, and Rieber et al pointed out the same cause as us (40,41).…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, the database lacks data regarding toxicity and quality of life. However, SBRT is generally well tolerated, with extremely low rates of clinically significant adverse effects, even within the elderly population . There were also relatively small numbers of patients who received SBRT compared with observation, likely because SBRT was in the early stages of adoption during the period of this study.…”
Section: Discussionmentioning
confidence: 96%
“…Helical tomotherapy (HT) may improve OAR sparing for those in very close proximity to the PTV, as is the case with central lung tumors [ 119 ]. Additionally, flattening filter-free (FFF) linear accelerators, capable of delivering dose rates up to four times that of conventional linear accelerators, may allow for shorter treatment delivery times and thus reduce the opportunity for intrafraction motion [ 120 ] and exposure of normal tissue to scattered dose outside the field [ 121 ]. Volume-adapted dosing strategies hold promise for decreased radiotherapy intensity for smaller tumors with similar tumor control, and consequently, reduced dose to OARs [ 122 ].…”
Section: Ways To Avoid Complicationsmentioning
confidence: 99%